Improving the Quality of CH3NH3PbI3 Films via Chlorobenzene Vapor Annealing. Issue 17 (21st May 2018) - Lei, Jie; Wang, Haoxu; Gao, Fei; Liu, Shengzhong
Abstract : Crystalline quality of perovskite materials is crucial to the photovoltaic performance of perovskite solar cells (PSCs). Herein, a chlorobenzene (CB) vapor annealing approach is introduced to prepare high quality CH3 NH3 PbI3 perovskite films. During the annealing process, the CB vapor diffuses into the CH3 NH3 PbI3 films and dissolves residual DMSO solvent, and volatilizes out of the CH3 NH3 PbI3 films to help residual DMSO solvent evaporate. This promotes the crystallization of the CH3 NH3 PbI3 films and the small grains integrate and merge together to form larger grains. The fabricated planar perovskite solar cells based on the CB vapor annealed CH3 NH3 PbI3 films have an average power conversion efficiency (PCE) of 17.9% and the highest PCE of 18.5%. In contrast, the planar perovskite solar cells fabricated using the traditional‐annealed CH3 NH3 PbI3 films give an average PCE of 16.4% and the highest PCE of 16.8%. The enhanced photovoltaic performance is due to the CH3 NH3 PbI3 film quality improvement, with higher crystallinity, larger grains, and longer carrier lifetime. Abstract : A chlorobenzene (CB) vapor annealing approach is introduced to prepare high quality CH3 NH3 PbI3 perovskite films. The fabricated planar perovskite solar cells based on the CB vapor annealed CH3 NH3 PbI3 films have the highest power conversion efficiency (PEC) of 18.5%. In contrast, the planar perovskite solar cells without CB vapor annealing give the highest PCE of 16.8%.